Polymerization-based signal amplification for paper-based immunoassays. Issue 3 (26th November 2014) - Badu-Tawiah, Abraham K.; Lathwal, Shefali; Kaastrup, Kaja; Al-Sayah, Mohammad; Christodouleas, Dionysios C.; Smith, Barbara S.; Whitesides, George M.; Sikes, Hadley D.
Abstract : Polymerization-based signal amplification is combined with an immunoassay for detection of a malaria antigen ( Pf HRP2) at paper surfaces. Abstract : Diagnostic tests in resource-limited settings require technologies that are affordable and easy to use with minimal infrastructure. Colorimetric detection methods that produce results that are readable by eye, without reliance on specialized and expensive equipment, have great utility in these settings. We report a colorimetric method that integrates a paper-based immunoassay with a rapid, visible-light-induced polymerization to provide high visual contrast between a positive and a negative result. Using Plasmodium falciparum histidine-rich protein 2 as an example, we demonstrate that this method allows visual detection of proteins in complex matrices such as human serum and provides quantitative information regarding analyte levels when combined with cellphone-based imaging. It also allows the user to decouple the capture of analyte from signal amplification and visualization steps.